Implementasi Metode Frame By Frame Untuk Perancangan Animasi 2D Aturan Berkendara Mobil Di Jalan Tol - Johanes M. Purba (STMIK Budi Darma, 2020)
New drivers who use a car sometimes find it difficult when crossing a toll road, because so far, most of the drivers, if they want to travel long distances, definitely use the toll road so they don't get stuck in traffic. However, when using toll roads, many do not know how good and safe driving rules are on the toll road, which will endanger themselves and other toll road users. To help find the solution to the rules for driving a car on toll roads so that they can be applied properly, it is built through 2D animation design. The animation design technique will use the Frame by Frame method which forms images of different objects then neatly arranged with the timing of the action of each to produce an animated story. Here the author tries to make 2D animations such as learning simulations that are easy to understand to help new drivers when crossing toll roads properly and safely.Keywords: Driving Rules, Frame By Frame, 2D Animation, Simulation